2018
DOI: 10.1038/s41598-018-24424-w
|View full text |Cite
|
Sign up to set email alerts
|

A Plasma Biomarker Panel of Four MicroRNAs for the Diagnosis of Prostate Cancer

Abstract: Prostate cancer is diagnosed in over 1 million men every year globally, yet current diagnostic modalities are inadequate for identification of significant cancer and more reliable early diagnostic biomarkers are necessary for improved clinical management of prostate cancer patients. MicroRNAs (miRNAs) modulate important cellular processes/pathways contributing to cancer and are stably present in body fluids. In this study we profiled 372 cancer-associated miRNAs in plasma collected before (~60% patients) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 74 publications
1
57
2
Order By: Relevance
“…Binary logistic regression was used to create the prediction model for combining the diagnostic effects of multiple miRNAs together. The P value 34 was calculated for each statistical analysis to indicate whether the null hypothesis can be refuted. 33…”
Section: Discussionmentioning
confidence: 99%
“…Binary logistic regression was used to create the prediction model for combining the diagnostic effects of multiple miRNAs together. The P value 34 was calculated for each statistical analysis to indicate whether the null hypothesis can be refuted. 33…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Matin at al. [128] discovered a four-miRNA panel (miR-98-5p, miR-152-3p, miR-326, and miR-4289) with increased levels in plasma samples from PC patients compared to healthy controls. Mahn et al [129] demonstrated that plasma miR-26a levels allowed discriminating between localized PC from benign prostate hyperplasia.…”
Section: Prostate Cancermentioning
confidence: 99%
“…This microRNA is usually found down-regulated in prostate tumor tissues [100]. On the other hand, another member of the miR-98 family, miR-98-5p, was recently recognized as an important candidate in early diagnosis of prostate cancer from plasma samples together with miR-4289, miR-326 and miR-152-3p [76,101]. The encouraging results on miRNAs are becoming palpable rapidly in the context of precision medicine.…”
Section: Mirnas Therapeutic Role In Prostate Cancermentioning
confidence: 99%